Effectiviness Of Whatsapp Medium As The Health Promotion Medium About Breast Milk - Mitra Asriani; Rusnawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2019)
The development of health promotion media in the management of disease prevention has been carried out. The limited use of commonly used health promotion media (leaflets, flipcharts, brochures, etc) and the emergence of the development of new internet-based information media provide hope for the development of further health promotion. This study aims to determine whether the Whatsapp medium influences the knowledge of mothers regarding exclusive breastfeeding. This study used a quasi-experimental design with group pre-test and post-test design. Using 50 samples selected by purposive sampling technique. Based on the results of the Wilcoxon signed-rank test, the average knowledge of exclusive breastfeeding before being given intervention is 3.44, this average knowledge increased by 3.88 points, reaching 7.32 with a p-value of 0,000 after being intervened using the Whatsapp medium. Knowledge about breastfeeding before being given intervention with Whatsapp medium was 5.10 and increased by 5.3 points after being given an intervention so that it reached 10.40 with a P-value of 0,000 or <of 0.05. the conclusion that can be drawn from this research is that WhatsApp social media is very effectively used as a health promotion media.